OPTIMIZATION OF LEVOFLOXACIN REMOVAL FROM AQUEOUS SOLUTION USING ELECTROCOAGULATION PROCESS BY RESPONSE SURFACE METHODOLOGY - S. J.Mohammed; M. J.Mohammed-Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the response surface methodology (RSM) to evaluate the effects of various experimental conditions on the removal of levofloxacin (LVX) from the aqueous solution by means of electrocoagulation (EC) technique with stainless steel electrodes. The EC process was achieved successfully with the efficiency of LVX removal of 90%. The results obtained from the regression analysis, showed that the data of experiential are better fitted to the polynomial model of second-order with the predicted correlation coefficient (pred. R2) of 0.723, adjusted correlation coefficient (Adj. R2) of 0.907 and correlation coefficient values (R2) of 0.952. This shows that the predicted models and experimental values are in good agreement. The results of the kinetic study showed that the second-order kinetic model was in good agreement with the experimental results and suggested that the mechanism of chemisorption controlled the LVX adsorption. The experimental results indicated that the adsorption of LVX on iron hydroxide flocs follows Sips isotherm with the value of the correlation coefficient (R2) of 0.937. Sips isotherm shows that both homogenous and heterogeneous adsorption can occur.